Acute kidney injury (AKI) in the intensive care unit (ICU) of Hospital Tengku Ampuan Afzan Kuantan (HTAA): Incidence, risk factors and outcome - Md Ralib, Azrina; Mat Nor, Mohd. Basri (2014)
Introduction: AKI is common and carries a high mortality rate. Most epidemiological studies were retrospective and were done in Western populations. A prospective study in a non-European population utilising the recent AKI consensus guideline is warranted. We aim to assess the AKI epidemiology in our local ICU. This will be the basis of future multicenter trial, and could provide data for the design of future trials. Methodology: This was a single centre, prospective observational study at the ICU of HTAA. The study was registered under the Malaysian NMRR and approved by the IIUM Ethics Committee (IREC 266). All patients more than 18 years being admitted to ICU and stayed for more than 48 hours were included in the study. Results: A total of 134 patients were recruited. 72 patients (54%) had AKI. 54 (40%) had a composite outcome of death or dialysis. Patients with AKI had longer duration of ICU stay (9.5+10.3 vs 6.3+5.5days,p=0.03). Those with AKI were also more likely to die or needed dialysis in 30 days compared to those without AKI (55.6% vs 21.7%, p<0.001). Of those with AKI, 42% were Stage 2 and 58% were Stage 3. Increasing stages of AKI is associated with increasing rate of death or dialysis. Discussion/Conclusion: AKI is common in our ICU, and is associated with higher morbidity and mortality. Of those with AKI, almost all presented with higher stages of AKI. None presented with Stage 1 AKI. This may reflect late presentation of illness on ICU admission in our population.